REAKTUALISASI PERAN KEBERAGAMAAN DALAM MENGATASI KRISIS MORAL PADA REMAJA DAN DEWASA AWAL - Sianly, Sekar; Dinanti Rusti, Dinda; Heriyati, Fika; Veriska; Arisanti, Devi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the reactualization of the role of religiosity in overcoming the moral crisis among adolescents and early adults in the modern era. Rapid social change, globalization, and digitalization have significantly influenced the moral development of young generations, leading to declining social ethics, weak self-control, and increasing deviant behavior. This research aims to analyze how religiosity can be contextualized and actualized as a relevant moral foundation in contemporary life. The study employs a qualitative approach with the type of library research by examining various scientific journals, books, and academic literature related to religiosity, morality, and youth development. Data were analyzed using content analysis through the stages of data reduction, presentation, and interpretation. The findings indicate that religiosity plays an important role in strengthening self-awareness, self-control, and character formation among adolescents and early adults. The reactualization of religious values through adaptive approaches, such as digital media utilization, family education, school-based religious activities, and positive social communities, can effectively address moral challenges in the digital era. Therefore, religiosity should not merely be understood as formal ritual practice, but also as a contextual and transformative value system that guides young people in maintaining moral integrity and social responsibility.